Augmented Horizons: Development and Impact of Augmented Reality on Atmospheric Education - Rindantiya, Riska Susmei; Haryanto, Zeni; Setyasih, Iya’ (CV Bumi Spasial, 2024)
Educational media serve as a supporting component in learning, offering benefits to enhance student engagement, interactivity, and interest in learning. The media employed should align with current advancements in science and technology, one of which is Augmented Reality (3D), a medium capable of projecting virtual objects into reality. This study aims to 1) Produce an AR media design for high school geography education on atmospheric topics, 2) Determine the feasibility of using AR-based media for such geography education. The creation of the Augmented Reality (3D) educational media utilizes the Borg and Gall (1989) model, which comprises ten development steps. This media creation employs Unity 3D software and supporting applications such as Vuforia, Cinema 4D, and Corel Draw. The development of this educational media resulted in two products: a smartphone application (for Android and iOS) named Cloud AR and its accompanying book, both of which meet UNESCO standards. Based on the research findings, the developed educational media is deemed suitable for use, with a score of 85.16% and classified in the suitable category.